The Influence of Behavioral Finance on Strategic Policy Decisions in a Textile Corporation in Beijing, China - WANG, XINXIU (Pacific International Journal, 2025)
China’s stance as a frontrunner in the global textile market brings the corporations in Beijing into the limelight, placing them at the forefront of the industry’s battle against a myriad of challenges, including market volatility, fluctuating consumer preferences, and heightened competitive pressures. As such, understanding the behavioral finance paradigms that govern the strategic policy decisions within a textile corporation in Beijing is not just an academic pursuit but a necessity for sustainable growth and market leadership. In this context, this study delves deep into the influence of behavioral finance on strategic policy decisions in a textile corporation located in Beijing, China. Drawing upon theories from behavioral finance such as mental accounting, herding, and overconfidence, among others, the research seeks to understand how these aspects mold policy decisions, potentially steering corporations towards a trajectory of sustainable growth. Furthermore, it aims to delineate the extent to which behavioral patterns and heuristics affect the judgment and choices of policy-makers, thereby influencing the corporation’s broader strategic blueprint.